Stunning - Shepard, Sara, 1977- (Shepard, Sara, 1977- Pretty little liars., 2012)
Struggling to return to normalcy after surviving Alison's attempt to kill them, Spencer, Aria, Emily and Hanna endure a series of disasters before realizing that they are being stalked by a new "A" who knows all of their secrets.